The other faces of the women in selected writings of Lualhati Bautista. - Mendoza, Regina Alcala
This descriptive study centers on the portrayal of gender roles and relations in society in the selected works of author and screenwriter Lualhati Bautista. Gender stereotyping in the mass media and the norms imposed by a patriarchal society are also noted. The depiction of the films by Lualhati Bautista implicitly argues that although traditional roles still exist, there are women who have already started thier journey towards liberation. This study combines ideas from a wide variety of feminisms and adapts them to interpret a particular setof women's subordinated yet resilient position within a male-dominated world. It counteracts the notion that the Filipina is still constrained by a backward mindset where she is expected to passive, obedient, submissive and self-sacrificing. This study shows the other faces of the Filipina where she delivers to be dynamic, assertive, strong and self-determining.